Association between maternal adiposity measures and adverse maternal outcomes of pregnancy: Systematic review and meta‐analysis. (25th April 2022) - Heslehurst, Nicola; Ngongalah, Lem; Bigirumurame, Theophile; Nguyen, Giang; Odeniyi, Adefisayo; Flynn, Angela; Smith, Vikki; Crowe, Lisa; Skidmore, Becky; Gaudet, Laura; Simon, Alexandre; Hayes, Louise
Summary: Maternal obesity increases pregnancy‐related risks. Women with a body mass index (BMI) ≥ 30 kg/m 2 are considered to be at risk and should receive additional care, although approximately half will have uncomplicated pregnancies. This systematic review aimed to identify early pregnancy measures of adiposity associated with adverse maternal health outcomes. Searches included six databases, reference lists, citations, and contacting authors. Screening and quality assessment were carried out by two authors independently. Random effects meta‐analysis and narrative synthesis were conducted. Seventy studies were included with a pooled sample of 89, 588 women. Meta‐analysis showed significantly increased odds of gestational diabetes mellitus (GDM) with higher waist circumference (WC) categories (1.40, 95% confidence interval [CI] 1.04, 1.88) and per unit increase in WC (1.31, 95% CI 1.03, 1.67). Women with GDM had higher WC than controls (mean difference [MD] 6.18 cm, 95% CI 3.92, 8.44). WC was significantly associated with hypertensive disorders, delivery‐related outcomes, metabolic syndrome, and composite pregnancy outcomes. Waist to hip ratio was significantly associated with GDM, hypertensive disorders, and delivery‐related outcomes. Fat mass, neck circumference, skinfolds, and visceral fat were significantly associated with adverse outcomes, although limited data were available. Our findings identify the need to explore how useful adiposity measures are at predicting risk in pregnancy, compared with BMI, to direct care to women with the greatest need.